2008
DOI: 10.1002/bdra.20471
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of NTDs with periconceptional multivitamin supplementation containing folic acid in China

Abstract: Periconceptional multivitamin supplementation containing folic acid can prevent the occurrence of NTDs with the beneficial effect dependent on the frequency and timing of the supplementation. Our study suggests that multivitamin supplement containing folic acid taken from a time point of 2 months before conception and continuing until completion of the second month after conception and taken more than five times per week can significantly reduce the risks of NTDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 25 publications
1
32
0
1
Order By: Relevance
“…Doses ranging from 360 μg (0.36 mg) (Kirke 1992) to 6000 μg (6 mg) (Chen 2008) a day have proven to be effective in preventing both occurrence and recurrence of NTDs; this wide response to supplementation may be determined by the baseline blood folate concentrations in each population. Improving nutrition surveillance in order to find the appropriate dose and supplementation scheme is crucial to promote a cost-effective public health policy that can reach a larger number of people.…”
Section: Summary Of Main Resultsmentioning
confidence: 99%
“…Doses ranging from 360 μg (0.36 mg) (Kirke 1992) to 6000 μg (6 mg) (Chen 2008) a day have proven to be effective in preventing both occurrence and recurrence of NTDs; this wide response to supplementation may be determined by the baseline blood folate concentrations in each population. Improving nutrition surveillance in order to find the appropriate dose and supplementation scheme is crucial to promote a cost-effective public health policy that can reach a larger number of people.…”
Section: Summary Of Main Resultsmentioning
confidence: 99%
“…If basic nutritional deficiency is the disease cause, nutritional supplements can reduce prevalence. Actually, nutrition intervention had been conducted in some Heshun province and the effects are remarkable (Chen et al 2008). The genetic factor is not concluded in environmental models but is left in model residuals.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Recent studies showed that prenatal multimicronutrient supplementation was associated with a significantly reduced risk of low birth weight when compared with iron-folic acid supplementation [62, 63]. Moreover, Chen et al proved that periconceptional multivitamin supplementation containing folic acid—two months before conception and until completion of the second month—containing folic acid can prevent the occurrence of NTDs [64]. These maternal and paternal nutritional deficiencies are probably multicausal.…”
Section: Characteristics Of Folate Deficiencymentioning
confidence: 99%